Manipulation of cytokinin level in the ergot fungus Claviceps purpurea emphasizes its contribution to virulence - Kind, Sabine; Hinsch, Janine; Vrabka, Josef; Hradilová, Michaela; Majeská-Čudejková, Mária; Tudzynski, Paul; Galuszka, Petr (Current genetics, 2018)
Pathogen-derived cytokinins (CKs) have been recognized as important virulence factor in several host-pathogen interactions and it was demonstrated multiple times that phytopathogenic fungi form CKs via the tRNA degradation pathway. In contrast to previous studies, the focus of this study is on the second step of CK formation and CK degradation to improve our understanding of the biosynthesis in fungi on the one hand, and to understand CK contribution to the infection process of Claviceps purpurea on the other hand. The ergot fungus Claviceps purpurea is a biotrophic phytopathogen with a broad host range including economically important crops causing harvest intoxication upon infection. Its infection process is restricted to unfertilized ovaries without causing macroscopic defense symptoms. Thus, sophisticated host manipulation strategies are implicated. The cytokinin (CK) plant hormones are known to regulate diverse plant cell processes, and several plant pathogens alter CK levels during infection. C. purpurea synthesizes CKs via two mechanisms, and fungus-derived CKs influence the host-pathogen interaction but not fungus itself. CK deficiency in fungi with impact on virulence has only been achieved to date by deletion of a tRNA-ipt gene that is also involved in a process of translation regulation. To obtain a better understanding of CK biosynthesis and CKs' contribution to the plant-fungus interaction, we applied multiple approaches to generate strains with altered or depleted CK content. The first approach is based on deletion of the two CK phosphoribohydrolase (LOG)-encoding genes, which are believed to be essential for the release of active CKs. Single and double deletion strains were able to produce all types of CKs. Apparently, log gene products are dispensable for the formation of CKs and so alternative activation pathways must be present. The CK biosynthesis pathway remains unaffected in the second approach, because it is based on heterologous overexpression of CK-degrading enzymes from maize (ZmCKX1). Zmckx1 overexpressing C. purpurea strains shows strong CKX activity and drastically reduced CK levels. The strains are impaired in virulence, which reinforces the assumption that fungal-derived CKs are crucial for full virulence. Taken together, this study comprises the first analysis of a log depletion mutant that proved the presence of alternative cytokinin activation pathways in fungi and showed that heterologous CKX expression is a suitable approach for CK level reduction.
Keywords: nemoci rostlin; Virulence; Cytokinin; cytokininy; Host-Pathogen Interactions; Plant Diseases; Claviceps; Cytokinin oxidase/dehydrogenase; Phosphoribohydrolase; Secale; interakce hostitele a patogenu; Cytokinins; Claviceps purpurea; žito